1999
DOI: 10.1111/j.1540-8175.1999.tb00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Imaging by Ultrasound in the Diagnosis of Regional Dysfunction of the Left Ventricle

Abstract: BACKGROUND: Regional strain rate in the left ventricle can be assessed by tissue Doppler velocity gradient and color mapped in real time. Regional contractility thus can be visualized and graded. To validate the method, we made a comparison with standard echocardiography. METHODS AND RESULTS: Fifteen patients with recent myocardial infarction were examined with the use of strain rate imaging (SRI). Velocity gradients were mapped by color. Gray-scale imaging was performed using the second harmonic mode. Cine lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 17 publications
1
86
0
Order By: Relevance
“…[1][2][3][4][5] The objectives of this study were to compare 2-dimensional Doppler echocardiographic and SRI features of patients with ABS and AMI and to evaluate systolic and diastolic parameters associated with myocardial viability.…”
Section: © 2009 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] The objectives of this study were to compare 2-dimensional Doppler echocardiographic and SRI features of patients with ABS and AMI and to evaluate systolic and diastolic parameters associated with myocardial viability.…”
Section: © 2009 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…1 Early experimental and clinical studies have shown that SRI can not only differentiate abnormal from normal myocardial contractility during the initial phase of an infarction but can also demonstrate subsequent recovery of transient ischemia. [1][2][3][4][5] The objectives of this study were to compare 2-dimensional Doppler echocardiographic and SRI features of patients with ABS and AMI and to evaluate systolic and diastolic parameters associated with myocardial viability.…”
Section: © 2009 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these techniques are based on analyzing ultrasound radiofrequency (RF) signals [5][6][7][8][9][10][11][12][13][14][15][16][17]. The first method known as acoustic quantification is based on the detection of the interface between the tissue and the blood in each image.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach known as Tissue Doppler Imaging (TDI) estimates velocity, and strain/strain-rate values of the LV myocardial wall. The different quantitative indices obtained from these parameters are proposed to characterize the RWM [12][13][14][15][16][17]. However, this method is very dependent on the signal to noise ratio of the Doppler data.…”
Section: Introductionmentioning
confidence: 99%